Identification of N-glycosylation in prolyl endoprotease from Aspergillus niger and evaluation of the enzyme for its possible application in proteomics - Sebela, Marek; Rehulka, Pavel; Kábrt, Jaromír; Rehulková, Helena; Ozdian, Tomás; Raus, Martin; Franc, Vojtech; Chmelík, Josef (Journal of mass spectrometry, 2009)
An acidic prolyl endoprotease from Aspergillus niger was isolated from the commercial product Brewers Clarex to evaluate its possible application in proteomics. The chromatographic purification yielded a single protein band in sodium dodecyl sulfate polyacrylamide gel electrophoresis providing an apparent molecular mass of 63 kDa and a broad peak (m/z 58,061) in linear matrix-assisted laser desorption/ionization (MALDI) time-of-flight (TOF) mass spectrometry (MS) indicating the glycoprotein nature of the enzyme. Indeed, a colorimetric assessment with phenol and sulfuric acid showed the presence of neutral sugars (9% of weight). The subsequent treatment with N-glycosidase F released a variety of high-mannose type N-glycans, which were successfully detected using MALDI-TOF MS. MALDI-TOF/TOF tandem MS analysis of glycopeptides from a tryptic digest of prolyl endoprotease unraveled the identity of the N-glycosylation site in the primary structure. The data obtained also show that the enzyme is present in its processed form, i.e. without putative signal and propeptide parts. Spectrophotometric measurements demonstrated optimal activity at pH 4.0-4.5 and also high thermostability for the cleavage at the C-terminal part of proline residues. In-solution digestion of standard proteins (12-200 kDa) allowed to evaluate the cleavage specificity. The enzyme acts upon proline and alanine residues, but there is an additional minor cleavage at some other residues like Gly, Leu, Arg, Ser and Tyr. The digestion of a honeybee peptide comprising six proline residues (apidaecin 1A) led to the detection of specific peptides terminated by proline as it was confirmed by MALDI postsource decay analysis.
Keywords: Molecular Sequence Data; sekvence aminokyselin; polysacharidy; proteomika; Autolysis; proteiny; prolyloligopeptidasy; koncentrace vodíkových iontů; serinové endopeptidasy; fungální proteiny; glykosylace; Peptide Fragments; Proteomics; Glycosylation; Fungal Proteins; Prolyl Oligopeptidases; Hydrogen-Ion Concentration; Amino Acid Sequence; Tandem Mass Spectrometry; peptidové fragmenty; Serine Endopeptidases; tandemová hmotnostní spektrometrie; molekulární sekvence - údaje; Aspergillus niger; Polysaccharides; autolýza; Proteins